2003
DOI: 10.1038/sj.onc.1207335
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic deletion of CDH1 as the inactivating mechanism of the wild-type allele in an HDGC tumour

Abstract: Mutations in CDH1, encoding E-cadherin, are the underlying genetic defect in approximately one-third of the hereditary diffuse gastric cancer (HDGC) families described so far. Tumours arising in these families show abnormal or absence of E-cadherin expression, following the model of tumour suppressor gene inactivation. A single study has been reported showing inactivation of the CDH1 wild-type allele in tumour cells from HDGC families either by promoter methylation or by somatic mutation. In order to find the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 24 publications
2
46
1
Order By: Relevance
“…137215), an autosomal dominant syndrome characterized by high susceptibility to early onset diffuse gastric carcinomas (Guilford et al, 1998). Heterozygous carriers of E-cadherin germline mutations frequently remain asymptomatic at least until the second decade of life, when inactivation of the remaining wild-type allele of the CDH1 gene occurs (Oliveira et al, 2004). This two hit inactivation mechanism is believed to determine the initiation of diffuse gastric cancer, consistent with the two-hit inactivation model proposed by Knudson (1971).…”
supporting
confidence: 55%
“…137215), an autosomal dominant syndrome characterized by high susceptibility to early onset diffuse gastric carcinomas (Guilford et al, 1998). Heterozygous carriers of E-cadherin germline mutations frequently remain asymptomatic at least until the second decade of life, when inactivation of the remaining wild-type allele of the CDH1 gene occurs (Oliveira et al, 2004). This two hit inactivation mechanism is believed to determine the initiation of diffuse gastric cancer, consistent with the two-hit inactivation model proposed by Knudson (1971).…”
supporting
confidence: 55%
“…When this wild-type allele becomes inactivated by a somatic second-hit molecular mechanism, this leads to biallelic inactivation of the CDH1 gene and the development of DGC [50][51][52]. Initial reports indicated that the second-hit that inactivates CDH1 in HDGC is most commonly promoter hypermethylation [50,52].…”
Section: Inactivation Of the 2nd Cdh1 Allelementioning
confidence: 99%
“…Aberrant E-cadherin staining patterns include absence of immunoreactivity as well as reduced membranous, "dotted" and cytoplasmic staining. The "dotted" staining pattern is probably due to the persistence of Ecadherin non-functional domains in the Golgi apparatus [51]. Abnormal immunoreactivity of E-cadherin has been described in precursor lesions (in situ SRCC and pagetoid spread of SRCs) as well as in early or advanced carcinomas, suggesting that the inactivation of Ecadherin is probably a key initiating event in HDGC tumourigenesis [60].…”
Section: Immunohistochemical Profile Of Hdgc and Its Relationship Witmentioning
confidence: 99%
See 2 more Smart Citations